PERANCANGAN DAN REALISASI RANGKAIAN CHARGER PADA PEMBANGKIT SELL SURYA UNTUK APLIKASI RUMAH TANGGA - Kasan, Nur (Jurnal Gamma, 2009)
Application of technology for the benefit of society by utilizing matahahari rays, where it ispossible use in locations that do not allow use of other alternative energy sources. Sunlight cangenerate electricity with solar cell power plant applications, this energy is almost never missing aday at certain locations with enough intensity radiation to produce electrical energy. Althoughcurrently still requires relatively high costs for solar cells, but by considering the factors easymaintenance and does not require routine maintenance every day, the charger circuit componentsreadily available in the market, may be set with the charging rate varies.In this scheme by considering the design of circuits that are sensitive to the setting conditionsof charging batteries in the charging condition or already full, with utilization of the op-amp as acomparator and SCR components as a component of the charging rate of electric energy to the solarbatteries, besides that also use power transistors as switches electronically at the time of chargingand at the electric charge on the batteries is full.The result of design equipment design charger with practical design with a very low cost, setthe charging rate can vary up to 10 Amperes and components are also easily available in the market.Tools charger allows for use on other plants originating from, for example, diesel generators,hydroelectric power, wind power, generating electricity from ocean waves, and so forth.